Effect of intravitreal dexamethasone implant (0.7mg) on intraocular pressure when used for macular edema in real world clinical practice - Sanjana Elfride F.; Sujatha Mohan; Ravichandran Kandaswamy (International Journal of Medical Research and Review, 2016)
Aim: To determine the effect of intravitreal dexamethasone implant 0.7mg (Ozurdex; Allergan, Inc.) on Intra ocular pressure when used for macular edema of varying etiology.Method: Retrospective non comparative clinical case study of 49 eyes of 49 patients who received a total of 49 injections of intravitreal dexamethasone implant (0.7mg) for macular edema of varying etiology such as diabetes mellitus, vein occlusion, noninfectious uveitis and miscellaneous causes. Best corrected visual acuity, baseline intraocular pressure, status of lens, previous vitrectomy were documented. Intraocular pressure was measured using applanation tonometry on the first, third and sixth month after the injection. All patients were followed up for a period of six months.Result: A total of 49 eyes met the inclusion criteria and were analyzed. The cause for macular edema was diabetes mellitus in 22 eyes,(49.9%)) , vein occlusion in 14 ( 28.6%) uveitis 7(14.3%) and miscellaneous causes in 6 (12.2%) eyes. Mean age of patient was 57 +/- 11.4 (mean +/_ SD) with male 29(59.2%) and female 20 (40.8%). Mean (± SE) BCVA and IOP were 0.62±0.36 log MAR and 14.57±2.5 mmHg, respectively, at baseline and at last follow up at 6 months 0.54+/_0.33 log MAR and 17.29+/_2.4mmHg. Nine (4.4%) patients presented with >5mmHg of increase in IOP from baseline and responded to medical management. No anti glaucoma surgery was performed on any of these patients. There was no progression of cataract and no endophthalmitis reported.Conclusion: Nine (4.4%) patients presented with a > 5mmHg in intraocular pressure. In real life clinical practice intravitreal dexamethasone (0.7mg) is a safe option for the treatment of macular edema from various causes.